Beginning Teacher Induction Research and Examples of Contemporary Practice - Arends, Richard I.; Rigazio-DiGilio, Anthony J. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2000)
This paper: reviews research on beginning teacher induction programs, summarizing previous reviews of the topic; identifies various state- and local-level induction programs, analyzing best practices that exist today; makes recommendations based on the research and on best practice for state and local policy development and for program development and implementation; and analyzes current trends in regard to the future development of teacher induction programs. Research review results include such findings as: released time and/or load reduction for mentors and beginners is essential; training mentors results in higher mentor effectiveness; and active principal support and involvement is necessary. The discussion of induction practices details district-based programs, a union-supported induction system, and state-based programs. Ten recommendations for induction programs include: obtain clarity about program goals and purposes; provide a research-based, ethically sound definition of effective teaching; and develop and implement an effective evaluation component for the induction program itself. Several common policy characteristics include: clarity of purpose; appropriate time frame for implementation; and political and financial commitment at all levels. Trends in teacher induction include: renewed interest in teacher induction and connecting induction to standards, licensing, and national certification. (Contains 104 references.) (SM)
ERIC Note: Paper presented at the Annual Meeting of the Japan-United States Teacher Education Consortium (JUSTEC) (July 2000). "This report summarizes a larger study on Teacher Induction and Mentoring conducted by Richard Arends and Nancy Winitzky in 1999.".
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Beginning Teacher Induction; Beginning Teachers; Elementary Secondary Education; Faculty Development; Mentors; School Districts; State Government; State Programs; Teacher Improvement; Teacher Qualifications; Reports, Research; Speeches/Meeting Papers